1986
DOI: 10.1073/pnas.83.10.3166
|View full text |Cite
|
Sign up to set email alerts
|

Human prostate-specific antigen: structural and functional similarity with serine proteases.

Abstract: The complete amino acid sequence of the prostate-specific antigen (PA) from human seminal plasma has been determined from analyses of the peptides generated by cyanogen bromide, hydroxylamine, endoproteinases Arg-C and Lys-C. The single polypeptide chain of PA contains 240-amino acid residues and has a calculated Mr of 26,496. An N-linked carbohydrate side chain is predicted at asparagine-45, and O-linked carbohydrate side chains are possibly attached to serine-69, threonine-70, and serine-71. The primary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
255
0
8

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(273 citation statements)
references
References 24 publications
9
255
0
8
Order By: Relevance
“…It has been reported that Zn 2q inhibits hK2 (Lovgren et al, 1999), hK3 (Watt et al, 1986), hK5 (Brattsand et al, 2005), hK7 (Franzke et al, 1996), and hK14 (Brattsand et al, 2005). The predicted Zn 2q -binding sites of hK2 and hK3 are composed of three His residues (Villoutreix et al, 1994;Lovgren et al, 1999), but sequence analysis shows that hK8 has only one His residue close to these corresponding positions ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Zn 2q inhibits hK2 (Lovgren et al, 1999), hK3 (Watt et al, 1986), hK5 (Brattsand et al, 2005), hK7 (Franzke et al, 1996), and hK14 (Brattsand et al, 2005). The predicted Zn 2q -binding sites of hK2 and hK3 are composed of three His residues (Villoutreix et al, 1994;Lovgren et al, 1999), but sequence analysis shows that hK8 has only one His residue close to these corresponding positions ).…”
Section: Discussionmentioning
confidence: 99%
“…PSA is a serine-protease secreted by epithelial prostate cells into the seminal fluid [19]. The presence of PSA in serum serves as a marker for the detection and monitoring of prostate carcinoma [20][21][22].…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%
“…Furthermore, recent progress in the theoretical framework of antigen recognition has resulted in a shift in our understanding of tumour-related antigens that can be rendered into specific targets of attack by the immune system: most of the peptides that are bound in the groove of an MHC molecule on tumour cells could essentially be a potential target determinant for immune attack. Prostate cancer presents a unique opportunity for inducing a tumour-specific attack by the immune system because a number of proteins, including prostate-specific antigen (PSA) and prostate-specific membrane antigen (PSM), are produced by cells of nearly all prostate tumours, but not by other cells or tissues of the individual [4,5].…”
Section: Introductionmentioning
confidence: 99%